(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
For the improvement of carrot cultivation in Egypt and because of the deterioration of the local Egyptian purple carrots, two novel colored (Purple and Deep Purple) F1 carrot hybrids were introduced for the first time from Netherland to be evaluated and compared to the broadly cultivated yellow Japanese F1 hybrid (Kuruda) under the Middle Egypt sandy soil growing conditions. The horticultural evaluation showed that the two purple hybrids have elongated thick roots and good vegetative growth and gave a very high yield of roots in two successive winter seasons of 2013/2014 and 2014/2015. The Deep Purple hybrid exceeded the other two hybrids in almost all studied chemical and horticultural characteristics. It showed about three folds of leaves fresh weight/plant, two folds of both root fresh weight/plant and yield/m2 when compared with Purple and Kuruda hybrids. The chemical analyses declared that the Purple and Deep Purple hybrids have higher contents of all estimated components and the Deep Purple hybrid had the highest values of total flavonoids (about two folds), total phenols (about 5-6 folds), antioxidant activity percentage (7-8 times), and total soluble solids percentage (1.5-2 times) than that of the yellow F1 hybrid “Kuruda”. These newly introduced two Purple and Deep Purple F1 hybrids may be very promising in production and processing purposes of purple carrots and good materials in carrot breeding programs in Egypt.